2013
DOI: 10.1039/c2lc40887b
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between cancer and immune cells: exploring complex dynamics in a microfluidic environment

Abstract: The reconstitution of a complex microenvironment on microfluidic chips is one of the cornerstones to demonstrate the improved flexibility of these devices with respect to macroscale in vitro approaches. In this work, we realised an on-chip model to investigate the interactions between cancer and immune system. To this end, we exploited mice deficient (Knock Out, KO) for interferon regulatory factor 8 (IRF-8), a transcription factor essential for the induction of competent immune responses, to investigate how I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 57 publications
0
126
0
1
Order By: Relevance
“…The microfluidic co-culture platforms were fabricated in PDMS (polydimethyl siloxane; Silgard 184; Dow Chemical, Detroit, MI), a bio-compatible optically transparent silicone elastomer, using standard soft lithographic techniques. Details of the fabrication protocols of these systems were described previously (Businaro et al, 2013). Access reservoirs were created using a suite of 8-mm dermal biopsy punch tools (Kai Medical, Honolulu, HI) and the final molded PDMS bonded to a glass microscope slide.…”
Section: Design Of Microfluidic Devicementioning
confidence: 99%
See 1 more Smart Citation
“…The microfluidic co-culture platforms were fabricated in PDMS (polydimethyl siloxane; Silgard 184; Dow Chemical, Detroit, MI), a bio-compatible optically transparent silicone elastomer, using standard soft lithographic techniques. Details of the fabrication protocols of these systems were described previously (Businaro et al, 2013). Access reservoirs were created using a suite of 8-mm dermal biopsy punch tools (Kai Medical, Honolulu, HI) and the final molded PDMS bonded to a glass microscope slide.…”
Section: Design Of Microfluidic Devicementioning
confidence: 99%
“…Extravasation analyses were performed using ImageJ software (http://rsbweb.nih.gov.ij/). Briefly, an ROI plug-in was used to measure the maximum distance reached by the tumor cells (with respect to microchannel borders) inside the splenocyte chamber (Businaro et al, 2013).…”
Section: Microscopy and Image Analysismentioning
confidence: 99%
“…[171] Preclinical testing currently relies on animal models before human studies, which are expensive and time consuming, and lack direct application to human physiology. [172] Recent studies incorporating microfluidics into the study of immune–tumor cell interactions have revealed the need for studying several cell types at the same time to evaluate the physiologically relevant interplay during the metastatic cascade, as the immune system dynamic changes over the course of tumor progression [172,173] (Figure 11).…”
Section: Microfluidic Technologies For Gbmmentioning
confidence: 99%
“…But physical removal of the cell monolayer could damage the cells, and thus could affect the detected result of cell migration. Businaro et al realized an on-chip model consisted of two center end-closed channels to investigate interactions between cancer and immune system (Businaro et al, 2013). This model elucidated the reciprocal interactions between heterogeneous but was difficult to process.…”
Section: Introductionmentioning
confidence: 99%